STRATEGI PENGEMBANGAN BISNIS PADA JM LAUNDRY: INTEGRASI SWOT MATRIX, BLUE OCEAN STRATEGY, DAN BUSINESS MODEL CANVAS - Dwi Wulandari; Hendra Lukito (Journal Publicuho, 2025)
This study explores laundry business development strategies through a comprehensive and innovative approach at JM Laundry in Payakumbuh City. Qualitative methods were used to identify the business environment through a SWOT matrix, design innovative value through the blue ocean strategy, and visualise the strategy through business model canvas mapping. Data collection was conducted through semi-structured interviews with the owner, employees, and customers of JM Laundry. Data analysis was performed using triangulation techniques—data reduction, data presentation, and conclusion drawing. The research findings indicate that identifying the business environment, creating innovative value, and modelling the current business facilitate JM Laundry in describing a strategic business model through the design of a new, applicable business model canvas. JM Laundry can optimize its reach into the dormitory, hotel, and apartment segments; utilize nanotechnology washing machines that can recycle used washing water; leverage AI (Artificial Intelligence) and IoT (Internet of Things) technologies; utilize subscription-based services; optimize the use of specialized applications; and offer additional services such as Laundry Plus Cafe, which provides a promising point of differentiation. The practical implications provide the laundry business with an innovative and sustainable business strategy model, thereby enhancing its competitiveness in the future.